MEMBINGKAI POLITIK BARU: STRATEGI KOMUNIKASI PARTIDU LIBERTASAUN POPULAR (PLP) DALAM DEMOKRASI TIMOR LESTE - Do Amaral, Joanico; Krisna Febriandy, Radians (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Partidu Libertasaun Popular (PLP) emerged as a new political alternative amidst the dominance of historical parties in Timor Leste. This research aims to reveal the PLP's political communication strategy in shaping the image of a reformist party that is in favor of the people. Through a qualitative approach and case study design, data were obtained through content analysis of campaign materials, semi-structured interviews with cadres, journalists, and young voters, and observation of party activities. The results showed that the PLP used a communication approach based on the narrative of reform, anti-corruption, and simplicity, which was framed consistently in various channels, including traditional and digital media. Issue framing is done by emphasizing the distance between the PLP and the old political elite, as well as highlighting the party's closeness to the grassroots. This communication strategy not only shapes positive perceptions of the PLP, but also strengthens the party's position in Timor Leste's post-conflict democratic landscape. These findings emphasize the importance of value-based political communication and new identities in creating alternative party competitiveness in developing democracies.